Degradação eletroquímica do cloranfenicol em reator de fluxo - Rezende, Luis Gustavo P.; Prado, Vânia M. do; Rocha, Robson S.; Beati, André A. G. F. [UNESP]; Sotomayor, Maria Del Pilar Taboada [UNESP]; Lanza, Marcos R. V. (Sociedade Brasileira de Química, 2010)
This paper reports a study of electrochemical degradation of the chloramphenicol antibiotic in aqueous medium using a flow-by reactor with DSA® anode. The process efficiency was monitored by chloramphenicol concentration analysis with liquid chromatography (HPLC) during the experiments. Analysis of Total Organic Carbon (TOC) was performed to estimate the degradation degree and Ion Chromatography (IC) was performed to determinate inorganic ions formed during the eletrochemical degradation process. In electrochemical flow-by reactor, 52% of chloramphenicol was degraded, with 12% TOC reduction. IC analysis showed the production of chloride ions (25 mg L-1), nitrate ions (6 mg L-1) and nitrite ions (4.5 mg L-1).
Electrochemical degradation of the chloramphenicol at flow reactor
Keywords: chloramphenicol; electrochemical reactor; DSA® anodes